The associations between parity, other reproductive factors, and osteoarthritis in women aged over 50 years; data from the Korean National Health and Nutrition Examination Survey V (2010-2012) - Su Mi Kim; Ju-Young Cheon; Yong-Gyu Park; Hae-Rim Kim; Jong Chul Shin; Hyun Sun Ko (Elsevier, 2017)
Objective: To evaluate the relationships between sociodemographic factors, reproductive history, and subsequent risk of osteoarthritis (OA) or pain of the hip, knee, and back in Korean women. Materials and Methods: This study included data of 5101 women aged over 50 years, taken from the Korean National Health and Nutritional Examination Survey V from 2010 to 2012. Women were stratified according to parity, as well as delivery mode. Multivariate logistic regression analysis was conducted to evaluate relationships between radiographic OA or symptomatically possible OA (back, knee, or hip), and historical factors. Results: Vaginal delivery was associated with an increased risk of symptomatic back OA [odds ratio (OR) 1.75, 95% confidence interval (CI) 1.062, 2.881] but was not associated with symptomatic knee and hip OA in adjusted analysis. Radiographically, vaginal delivery was not associated with risks of back and knee OA, but was negatively associated with hip OA (OR 0.184, 95% CI 0.039, 0.863), compared to cesarean delivery. High parity (over 5) was associated with radiographic knee OA (OR 1.328, 95% CI 1.006, 1.754) in adjusted analysis. High parity (over 3) was associated with symptomatic back OA. Conclusion: Parity was associated with higher risk of radiographic knee OA. Vaginal delivery was positively associated with symptomatic back OA, but negatively associated with radiographic knee OA. Further study is required to evaluate the mechanism between delivery mode and subsequent OA.